DISTRIBUSI LOGAM TIMBAL (Pb) PADA TANAMAN WEDELIA (Wedelia trilobata (L.) Hitch) AKIBAT EMISI KENDARAAN BERMOTOR DI BEBERAPA JALAN KOTA SAMARINDA - Amalia Saleha; Alimuddin -; Rahmat Gunawan (JURNAL KIMIA MULAWARMAN, 2013)
The research has done of "The distribution of lead (Pb) on wedelia plants contaminated by vehicular emission on several main road in samarinda”. This study aimed to determine the metal concentrations of lead in roots, flowers and leaves of plants wedelia at several locations in the city of Samarinda on PM Noor Street, Wahid Hasyim Street, Pahlawan Street, AW Syahrani Street, and Belatuk Street (control location) were the different traffic density and the treatment of leaching on levels of lead found in wedelia plants. The concentrations of lead metal on wedelia plants were measured using an Atomic Absorption Spectrophotometer (AAS) at a wavelength of 283.3 nm. The results showed that The highest levels of Pb obtained on PM Noor and lowest on Belatuk, were the traffic density is high concentration of lead is absorbed more than low traffic density. And the treatment of non-leaching and leaching concentrations obtained difference was not significant, indicating leaching did not significantly affect the concentration of Pb on plants.